Produção de videoaulas com tradução em libras: tecnologia assistiva no ensino de Química - Moraes, Isabele Fernanda Silva de (Brasil, 2024)
Digital tools play a significant role in chemistry education, serving as widely adopted resources for students to grasp abstract concepts. Among these resources, YouTube stands out as a platform rich in educational content. However, when it comes to addressing the needs of the deaf community in the context of chemistry, the availability of resources is notably limited. One possible approach to mitigate the challenges faced by the deaf community is the implementation of assistive technologies in education, encompassing children, youth, and adults with diverse disabilities. The primary objective of this research is to assess the use of assistive technology resources specifically designed for deaf students in the context of chemistry classes. Additionally, an effort was made to create chemistry video lessons with sign language interpretation (Libras). This research adopts a qualitative approach, aiming to understand the objectives and values of the participants involved in the educational process. To carry out this project, the epistemological basis of action research was employed as the methodology. Three video lessons were developed covering the following topics: Physical Transformations of Matter, Atomic Models, and Chemical Bonds. Each video lesson was divided into three segments: Introduction, presenting the lesson's topic and relevant questions; Development, where concepts were dynamically explained with everyday examples; and Conclusion, encouraging reflection on the lesson and the content's importance for the learning process. The video lessons underwent a validation process with chemistry teachers and members of the deaf community. One observation made during validation highlighted the importance of students' prior knowledge for comprehending the content of the video lessons. Regarding the logical sequence presented in the videos, all teachers expressed acceptance with this aspect. In the question regarding the relevance of incorporating images and animations into video lessons, the deaf community unanimously asserted that this element played a fundamental role in facilitating the understanding of concepts in the field of Chemistry. The implementation of the video lesson with the didactic sequence made the teaching-learning process more dynamic and appealing to the student, as the video lesson was used for review in this process. These results reflect the importance of integrating assistive technology into chemistry classes to meet the needs of the deaf community, providing an inclusive and effective approach to teaching this chemistry discipline.